2013
DOI: 10.1055/s-0032-1328382
|View full text |Cite
|
Sign up to set email alerts
|

Central Corneal Regularization - Optimization of Uncorrected Visual Acuity in Keratoconus Patients

Abstract: Combined corneal cross-linking and central corneal regularization treatment has the potential to achieve a clinically significant improvement of uncorrected visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Pre-operative assessment included uncorrected (UDVA) and corrected (CDVA) distant visual acuity, cycloplegic and non-cycloplegic manifest refraction, and slit lamp examination, including dilated fundoscopy and measurement of intraocular pressure. Scheimpflug-based Imaging corneal topo/tomography, obtained by Precisio (iVis Technologies S. r. l., Taranto, Italy), was used for a preoperative diagnostic as the basis for custom surgery planning and pre- and postoperative structural and optical analysis, including the evaluation of HOCMAs [6, 8]. For the measurement of the latter, a parameter describing optical regularity of the corneal surface, named HOCMAs, was introduced by the manufacturer of the Precisio.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pre-operative assessment included uncorrected (UDVA) and corrected (CDVA) distant visual acuity, cycloplegic and non-cycloplegic manifest refraction, and slit lamp examination, including dilated fundoscopy and measurement of intraocular pressure. Scheimpflug-based Imaging corneal topo/tomography, obtained by Precisio (iVis Technologies S. r. l., Taranto, Italy), was used for a preoperative diagnostic as the basis for custom surgery planning and pre- and postoperative structural and optical analysis, including the evaluation of HOCMAs [6, 8]. For the measurement of the latter, a parameter describing optical regularity of the corneal surface, named HOCMAs, was introduced by the manufacturer of the Precisio.…”
Section: Methodsmentioning
confidence: 99%
“…In order to gain a better control of visual outcomes in addition to strengthening the cornea, CXL has been combined with other procedures such as laser vision correction, implantation of corneal ring segments, or use of phakic or aphakic intraocular lenses, thus improving eye optics. It seems that corneal surface ablation, performed in the same session as CXL or sequentially, has been the most popular of those procedures [1, 6, 7]. The combined treatment consisting of CXL preceded by a minimally invasive customized trans-epithelial corneal regularization seems to be a promising approach to freezing the keratoectatic process in an optically regularized cornea and achieving a potentially stable improvement of the quality of vision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a protocol in the name of "Central Corneal Regularization (CCR)" on the iVis Suite customized excimer laser ablation treatment platform (iVis Technologies S. r. l., Taranto, Italy) was tried with keratoconus patients (Amsler-Krumeich stage I-II) and was shown to improve both uncorrected and corrected visual acuity. 71,72 A subsequent comparative study also showed that the combination of the CCR/PRK approach with C-CXL results in a more effective reduction in higher-order aberrations and Kmax than what can be achieved with C-CXL alone. 73 Kanellopoulos AJ modified the Athens protocol by incorporating topographically guided varied pattern C-CXL into the protocol thereby reducing the amount of tissue that has to be removed by PRK.…”
Section: Advances In Treatmentmentioning
confidence: 97%
“…The concept of CCR and the iVIS Suite™ platform modules are described in detail elsewhere [19]. In brief, a PrecisioHD™ Scheimpflug tomographer was used to acquire corneal elevation maps, each consisting of 39, 000 measurement points with an auto-validated repeatability of ≤3 μm [20].…”
Section: Surgical Techniquesmentioning
confidence: 99%